The Intercultural Approach in Japanese Speaking Learning Activities - Cut Erra Rismorlita (Makassar State University, 2021)
Abstract. The aim of the study was to get deeply the implementation intercultural approach in Japanese speaking learning activities at senior high school. The research method is qualitative using direct observation. While the process of collecting data used documentation, video record, field note, the interview is appropriate with the research setting. The result of research found that Japanese speaking activities inside and outside the classroomhave some components, namely learning method implementation, the role of teacher and students, the role of native speaker teacher, and the material of learning. It has combined the linguistics aspect and culture to increase students’ comprehension of Japanese language and culture. Keywords: Intercultural Approach, Japanese Speaking, Learning Activities